Clinical Characteristics and Outcome of Patients with Multiple Intracranial Aneurysms from a University Hospital in Nepal - Sharma, Mohan Raj; Kafle, Prakash; Rajbhandari, Binod; Pradhanang, Amit Bahadur; Kumar, Shrestha Dipendra; Sedain, Gopal (Asian Journal of Neurosurgery, 2022)
Objective The risk factors, management strategies, and outcomes of patients with multiple intracranial aneurysms (MIAs) are different compared with that of patients with a single aneurysm. Data are scarce regarding patients with MIAs from developing countries. The objective of this study was to describe the clinical characteristics, management strategies, and outcomes of patients treated microsurgically from Nepal.Methods The clinical records of patients confirmed to have MIAs and microsurgically clipped between July 2014 and December 2019 were retrospectively reviewed. Data on demographic and clinical characteristics, computed tomography findings, multiplicity and location of aneurysms, management strategies, and the 1-year outcome were abstracted and analyzed.Results Two hundred cerebral aneurysms were microsurgically clipped in 170 consecutive patients during the study period. Twenty-six (13.0%) patients harbored 60 aneurysms. The mean age of the patients was 58.5 (43–73) years. Smoking and hypertension were found in 20 (76.9%) and 16 (61.5%) patients, respectively. The majority of patients [17 (65.4%)] were in good grades at presentation. Twenty-one patients had two aneurysms, four had three aneurysms, and one patient had five aneurysms. The middle cerebral artery was the commonest (20) followed by distal anterior cerebral artery (14) and anterior communicating artery (13) involved in multiplicity. A single-stage surgery was performed on 17 patients. Serial clipping was performed in six patients. In three patients, a single aneurysm on the contralateral side was left untreated for various reasons. The favorable outcome was achieved in 23 (88.5%) patients whereas three (11.5%) patients had an unfavorable outcome. One patient died.Conclusion The demographic and clinical characteristics of patients in our series are comparable with those described in the published literature from other countries. With an individualized treatment strategy, an acceptable outcome can be achieved in the majority of the patients.
Keywords: microsurgical clipping; multiple intracranial aneurysms; Nepal; subarachnoid hemorrhage